Quality evaluation of the cassava core collection at CIAT - Wheatley, Christopher C.; Orrego Aristizábal, JI; Sánchez, T.; Granados F, E (International Center for Tropical Agriculture, 1993)
A core collection of 630 cassava clones has been established at CIAT, representative of the complete germplasm collection of 5169 clones. All available clones in the core collection (560) were analysed for dry matter and total cyanogen contents, and starch was extracted for determination of amylose values. Root parenchyma dry matter and total cyanogen contents had maximum and minimum values of 49-13 and 1041-7 mg kg-1 (fresh weight basis) respectively. Mean and median parenchyma total cyanogen contents were 102 and 55 mg kg-1 (fresh weight basis) respectively. Significant positive correlations were found between dry matter contents in peel and parenchyma, and between total cyanogens in peel and parenchyma. Maximum and minimum amylose values of 28 and 15 were found. Cluster analysis identified clones containing both high root dry matter (>43) and low parenchyma total cyanogen contents (<20 mg kg-1). Significant differences in starch functionality were found between clones with high and low total cyanogen contents.